27 million years of sediment production in the Omo River catchment and contribution to the sedimentation in the Turkana Depression (EARS, Kenya/Ethiopia) - Perrine Poirier; Alexis Nutz; Vincent Godard; Théa Ragon; Ghislain Gassier; Mathieu Schuster (Journal of African Earth Sciences, 2026)

Synthesis, antibacterial activity and molecular docking studies of foetidumin A derivatives - Fadil Y. Nankam; Hermine W. Nono; Arno R. D. Nanfack; Michael H. K. Kamdem; Elodie G. Matheuda; Ervira K. Djoukam; Marthe C. D. Fotsing; Edwin M. Mmutlane; Xavier Siwe Noundou; Vincent P. N. Nziko; Maurice D. Awouafack; Derek T. Ndinteh; et al. (Natural Product Research, 2026)

Tea, coffee, and cocoa delay milk gastric coagulation in a biomimetic in vitro system (NERDT™) by hindering both acid- and pepsin-induced milk gelation - Isuri A. Jayawardana; Amélie Deglaire; Olivia Ménard; Marie-Francoise Cochet; Yann Le Gouar; Jordane Ossemond; Vincent Mathieu; Martine Morzel; Didier Dupont; Steven Le Feunteun (Food Research International, 2026)

Peripheral microRNA signature in genetic frontotemporal dementia—findings from the GENFI initiative - Chiara Fenoglio; Maria Serpente; Marina Arcaro; Tiziana Carandini; Luca Sacchi; Manuela Pintus; Vittoria Borracci; Giulia Giudici; Marta Rigoni; Paola Muti; Laura Ghezzi; Arabella Bouzigues; et al. (GeroScience, 2026)
Frontotemporal dementia (FTD) is a neurodegenerative disease characterized by significant clinical and genetic heterogeneity, with approximately 40% of cases linked to hereditary genetic mutations, including MAPT , GRN , and C9ORF72 . Recently, microRNAs (miRNAs) have emerged as key regulators of cellular processes related to neurodegeneration and as potential biomarkers for FTD. However, their relevance in presymptomatic stages remains poorly understood. We conducted a miRNA expression analysis using TaqMan OpenArray® panels on blood samples collected from 171 individuals, including symptomatic mutation carriers (SMC), presymptomatic carriers (PMC), and healthy non-carriers (NC). Dysregulated miRNAs were validated and bioinformatic tools were used to identify potential associated molecular pathways. In C9ORF72 , miR-20b-5p and miR-223-5p were significantly upregulated in SMC (fold regulation over NC: 2.418 p = 0.0336 and 7.829 p < 0.0264 respectively) and PMC (5.518, p < 0.0001 and 3.941, p < 0.0001 respectively). In GRN mutation carriers, miR-28-3p was altered in both SMC and PMC (fold regulation over NC: 1.484 p < 0.050 and 3.287, p < 0.050). In MAPT mutation carriers, miR-28-5p, miR-192-3p, miR-25-3p, and miR-532-3p were altered only in SMC (fold regulation over NC: 1.496 p < 0.050, 1.911 p = 0.006, 1.468 p < 0.05, and 0.728 p < 0.05). Bioinformatic analysis revealed enrichment of pathways related to neurodegeneration and synapse impairment. These results suggest that miRNA expression levels are deregulated in mutated SMC, in C9ORF72 and GRN PMC. Notably, miR-20b-5p, miR-223-5p, and miR-28-3p were increased in preclinical stages of the disease, supporting their role as early biomarkers for C9ORF72 -FTD and GRN -FTD. Conversely, alterations in MAPT carriers appeared only in symptomatic stages, suggesting a different involvement in disease progression.

Impact of volcanic emissions on the air quality during the 2021 volcanic eruption of Tajogaite, La Palma: Implications for population exposure to volcanic pollutants - Julia Eychenne; Raphael Paris; Agnès Borbon; David Jessop; Mathieu Gouhier; Guillem Gisbert Pinto; Antoni Calafat; Aurélie Colomb; José-Luis Fernandez-Turiel; Vincent Gaussen; Clara Gorce; Séverine Moune; et al. (Science of The Total Environment, 2026)

Advanced strategies for discrete simulations with three-dimensional R-shapes in rockable framework - Vincent Richefeu; Gaël Combe; Lhassan Amarsid; Raphaël Prat; Jean-Mathieu Vanson; Saied Nezamabadi; Patrick Mutabaruka; Jean-Yves Delenne; Farhang Radjaï (Computer Physics Communications, 2026)

Different temperature responses of mountain rockwalls, soils, and lakes to summer heat waves - Rosalie Bruel; Florent Arthaud; Florence Magnin; Raphaëlle Napoleoni; Colin Van Reeth; Vincent Augé; Clotilde Sagot; Mathieu Fructus; Carole Birck; Philippe Choler (Regional Environmental Change, 2026)
Mountain ecosystems are highly sensitive to climate variations. At fine spatial scales, high-elevation microclimates play a critical role in shaping biodiversity, hydrological processes, and ecosystem services, while also influencing the occurrence of natural hazards such as landslides, avalanches, and floods. Heat waves, which have been increasing in frequency and intensity due to global climate change, present significant challenges to these vulnerable environments. This study examines the impacts of summer heat waves on mountain microthermal conditions in three compartments: rockwalls, soils, and lakes. We assembled data across a latitudinal and elevational gradient in the French Alps including years of two recent heat wave events (2015 and 2022). We calculated thermal indicators to evaluate the buffering or amplifying effects of the atmospheric signal on the investigated compartments. The average summer temperature and the growing/thawing degree days were more responsive to heat waves than the phenological indicator (e.g., spring mixing date in lakes) and maximum temperature. We found significant anomalies for both the 2015 and 2022 heat waves across almost all compartments and indicators. Lakes tended to amplify atmospheric temperatures (especially in 2022) whereas rockwalls and soils tended to buffer them. However, residues from the relationship between compartment and atmospheric temperatures were large during heat waves, suggesting that these events may reduce the compartments’ buffering capacity. Our study underscores the importance of long-term monitoring of microthermal conditions to provide a more integrative assessment of mountain ecosystem response to extreme meteorological events. Graphical abstract

Stormwater sediment composition: bio-physico-chemical signature of organic-rich sediments and practical implications - Chabert Milèna; Tedoldi Damien; Zhan Qiufang; Gautier Mathieu; Fardel Alexandre; Lakel Abdelkader; Lipeme Kouyi Gislain; Chatain Vincent (Journal of Soils and Sediments, 2026)

Clinical spectrum of ICU-acquired invasive pulmonary aspergillosis according to SARS-CoV2 infection: a multicenter prospective cohort study - Florian Reizine; Mattéo Mauget; Nicolas Massart; Yannick Fedun; Anaïs Machut; Charles-Hervé Vacheron; Anne Savey; Arnaud Friggeri; Alain Lepape; Melissa Abbes; Abdelkrim Abdelmalek; Francoise Adema; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Effect of consumption temperature of whole milk on in vitro gastric digestion using a biomimetic digestion simulator - Jiajun Feng; Jeehyun Lee; Vincent Mathieu; Yann Le Gouar; Romain Jeantet; Didier Dupont; Steven Le Feunteun (Food Research International, 2026)

The Dynamic Interaction between Procedural Learning and Resting-State Functional Connectivity in Self-Limited Focal Epilepsies - Coralie Rouge; Elodie Juvené; Dorine Van Dyck; Soléane Gander; Odile Feys; Pauline Van Gyseghem; Mathieu Bourguignon; Vincent Wens; Xavier De Tiège; Alec Aeby; Charline Urbain (Brain Topography, 2026)

Effects of 1-MCP and ULO on quality parameters, bioactive compounds, volatiles and sensory quality of Williams pears (Pyrus communis L.) during long-term storage. - Christophe Aubert; Guillaume Chalot; Valentine Cottet; Vincent Mathieu-Hurtiger (Postharvest Biology and Technology, 2025)

A biomimetic hybrid soft/rigid robotic masticator simulating Oral processing of solid foods - Avila-Sierra Alejandro; Bussiere Jérôme; Mathieu Vincent; Saint-Eve Anne; Peyron Marie-Agnès; Kobayashi Yoshikazu; Ramaioli Marco (Food Research International, 2025)

Implementation of an ultrasound method on a custom-built tribometer to investigate tongue-palate friction during food oral processing - Miodrag Glumac; Véronique Bosc; Paul Menut; Marco Ramaioli; Frédéric Restagno; Sandrine Mariot; Vincent Mathieu (Food Research International, 2025)

Comparison of high-fidelity transport code predictions against the NECTAR intra-pin reaction rate measurements - Tom Mager; Mathieu Hursin; Kyle Vaughn; Sooyoung Choi; Brendan Kochunas; Thomas Ligonnet; Vincent Lamirand; Oskari Pakari; Carlo Fiorina; Andreas Pautz (Annals of Nuclear Energy, 2025)

Oral-stomach sampling as an alternative to rumen canula for the inoculation of in vitro batch fermentation systems - Vincent Niderkorn; Sandra Point; Angelique Torrent; Pierre Nozière; Mathieu Silberberg; Anne Boudon (Animal Feed Science and Technology, 2025)

Citizen Science in Space and Atmospheric Sciences: Opportunities and Challenges - Maxime Grandin; Vincent E. Ledvina; Sophie Musset; Noora Partamies; Nathaniel A. Frissell; Emma Bruus; Keri A. Nicoll; Hripsime Mkrtchyan; Bea Gallardo-Lacourt; Lucilla Alfonsi; Marius O. Jonassen; Daniel Whiter; et al. (Surveys in Geophysics, 2025)
Citizen science (also referred to as participatory science or community science), in which members of the general public contribute to scientific research, is not a new concept, as early examples of such studies can be found a couple of centuries ago. With the advancement of technology in an increasingly connected world, it has never been easier to engage citizen scientists in research projects. In this paper, we review citizen science initiatives and projects in the fields of atmosphere and space physics, including both early observation campaigns prior to the twenty-first century and recent projects. Ongoing initiatives take a broad range of forms, from the collection of data by citizen scientists to their involvement in the data analysis process and to the hosting of instruments in non-scientific public structures. We also discuss some of the challenges specific to citizen science, such as training citizen scientists, maintaining their engagement, ensuring reciprocity, managing citizen science data, interfacing the academic and citizen scientist communities, and funding citizen science. To these challenges we suggest possible solutions, and we highlight the unique opportunities offered by recent software and hardware developments. These game-changing opportunities are foreshadowing the dawn of a new era for citizen science – and hence for science in general and atmosphere and space physics in particular.

Cognitive and neuroimaging outcome of very prodromal dementia with Lewy bodies - Frédéric Blanc; Vincent Bouteloup; Claire Paquet; Marie Chupin; Florence Pasquier; Audrey Gabelle; Mathieu Ceccaldi; Paulo Loureiro de Sousa; Pierre Krolak-Salmon; Renaud David; Clara Fischer; Jean-François Dartigues; et al. (GeroScience, 2025)

Geothermal resources of Réunion Island, Indian Ocean, studied by noble gas systematics in thermal springs - Emilie Roulleau; Daniele L. Pinti; Vincent Famin; Bhavani Bénard; Nicolas Vinet; Angeline Bulot; Céline d'Angelo; Mathieu Claudon; Joséphine Gambiez; Noémie Bouche (Journal of Volcanology and Geothermal Research, 2025)

Effects of home-based exercise with or without cognitive training on cognition and mobility in cardiac patients: A randomized clinical trial - Florent Besnier; Emma Gabrielle Dupuy; Christine Gagnon; Thomas Vincent; Tudor Vrinceanu; Caroll-Ann Blanchette; Josep Iglesies-Grau; Kathia Saillant; Malorie Chabot-Blanchet; Sylvie Belleville; Martin Juneau; Paolo Vitali; et al. (GeroScience, 2025)

CORTEX experiments – Part I: Modulation campaigns in AKR-2 & CROCUS for the validation of neutron noise codes - Vincent Lamirand; Alexander Knospe; Klemen Ambrožič; Sebastian Hübner; Carsten Lange; Oskari Pakari; Fanny Vitullo; Adolfo Rais; Joachim Pohlus; Uwe Paquee; Christoph Pohl; Nicolas Weiss; et al. (Annals of Nuclear Energy, 2025)

Nationwide operational mapping of grassland first mowing dates combining machine learning and Sentinel-2 time series - Henry Rivas; Hélène Touchais; Vincent Thierion; Jerome Millet; Laurence Curtet; Mathieu Fauvel (Remote Sensing of Environment, 2024)

CORTEX experiments, Part II: Postprocessing of neutron noise time series to determine reliable mean and uncertainties - Klemen Ambrožič; Alexander Knospe; Oskari Pakari; Sebastian Hübner; Mathieu Hursin; Carsten Lange; Adolfo Rais; Axel Laureau; Andreas Pautz; Vincent Lamirand (Annals of Nuclear Energy, 2024)

From planning to implementation: a multi-stakeholder partnership for managing plant invasions in tropical island ecosystems - Mathieu Rouget; Pauline Fenouillas; Emilie Cazal; Margot Caubit; Cédric Ajaguin Soleyen; Eve Balard; Antoine Becker-Scarpitta; Laurent Calichiama; Gael Karczewski; Christophe Lavergne; Benoît Lequette; Roxane L’Horset; et al. (Biological Invasions, 2024)

Using a natural salivary substitute to improve the swallowability of semi-solid foods: An in vitro and in vivo study - Yurixy Bugarin-Castillo; Pascale Bou Fadel; Anne Saint-Eve; Marco Ramaioli; Vincent Mathieu (Food Hydrocolloids, 2024)

No Future Growth Enhancement Expected at the Northern Edge for European Beech due to Continued Water Limitation - Stefan Klesse; Richard L. Peters; Raquel Alfaro‐Sánchez; Vincent Badeau; Claudia Baittinger; Giovanna Battipaglia; Didier Bert; Franco Biondi; Michal Bosela; Marius Budeanu; Vojtěch Čada; J. Julio Camarero; et al. (Global Change Biology, 2024)
With ongoing global warming, increasing water deficits promote physiological stress on forest ecosystems with negative impacts on tree growth, vitality, and survival. How individual tree species will react to increased drought stress is therefore a key research question to address for carbon accounting and the development of climate change mitigation strategies. Recent tree‐ring studies have shown that trees at higher latitudes will benefit from warmer temperatures, yet this is likely highly species‐dependent and less well‐known for more temperate tree species. Using a unique pan‐European tree‐ring network of 26,430 European beech ( Fagus sylvatica L. ) trees from 2118 sites, we applied a linear mixed‐effects modeling framework to (i) explain variation in climate‐dependent growth and (ii) project growth for the near future (2021–2050) across the entire distribution of beech. We modeled the spatial pattern of radial growth responses to annually varying climate as a function of mean climate conditions (mean annual temperature, mean annual climatic water balance, and continentality). Over the calibration period (1952–2011), the model yielded high regional explanatory power ( R 2 = 0.38–0.72). Considering a moderate climate change scenario (CMIP6 SSP2‐4.5), beech growth is projected to decrease in the future across most of its distribution range. In particular, projected growth decreases by 12%–18% (interquartile range) in northwestern Central Europe and by 11%–21% in the Mediterranean region. In contrast, climate‐driven growth increases are limited to around 13% of the current occurrence, where the historical mean annual temperature was below ~6°C. More specifically, the model predicts a 3%–24% growth increase in the high‐elevation clusters of the Alps and Carpathian Arc. Notably, we find little potential for future growth increases (−10 to +2%) at the poleward leading edge in southern Scandinavia. Because in this region beech growth is found to be primarily water‐limited, a northward shift in its distributional range will be constrained by water availability.

Greener green: The environmental impacts of the Canadian cannabis industry - Vincent Desaulniers Brousseau; Benjamin P. Goldstein; Mathieu Lachapelle; Ilies Tazi; Mark Lefsrud (Resources, Conservation and Recycling, 2024)

Plant distribution and conservation in mediterranean islands’ lentic wetlands: there is more than aquatic species - Mauro Fois; Alba Cuena-Lombraña; Mathieu Artufel; Vincent Attard; Salvatore Cambria; Krista Farrugia; Michela Marignani; Pietro Minissale; Andrea Pace; Saverio Sciandrello; Eva Tankovic; Gianluigi Bacchetta (Biodiversity and Conservation, 2024)
This study investigates the distribution and conservation status of plant species in lentic wetlands of Mediterranean islands. Field data on vascular macrophytes were collected from the online national databases of the “Conservation of the island wetlands of the Mediterranean Basin” (MedIsWet). A comprehensive inventory of wetlands was conducted, and information on the main anthropogenic impacts and conservation priorities was compiled. In addition to all vascular hygro- and hydrophytes, we retained information on those species typically adapted to environments with intermittent or temporary wetness. A significant knowledge gap regarding the distribution and conservation of plant species in Mediterranean wetlands was found. A lower endemism rate was observed particularly in coastal wetlands. However, approximately 25% of species, mainly with relatively wide distribution, were identified as endangered or with unknown conservation status. Including all macrophytes adapted to seasonal wetness is crucial when considering wetland conservation efforts. The research emphasised the importance of considering diverse wetland types, including seasonal and permanent, natural and artificial, for effective plant conservation. Artificial wetlands emerged as potential habitats with considerable biodiversity conservation value. This study provides a comprehensive inventory of wetlands and valuable insights into the distribution, ecology, and conservation relevance of aquatic macrophytes in Mediterranean islands. The research enhances our understanding of biogeographic patterns and processes, offers critical information for the management and conservation of Mediterranean island wetlands, and presents a replicable approach that can be applied to other wetland contexts.

A systematic approach for detecting abrupt shifts in ecological timeseries - Mathieu Pélissié; Vincent Devictor; Vasilis Dakos (Biological Conservation, 2024)

The DeepFaune initiative: a collaborative effort towards the automatic identification of European fauna in camera trap images - Noa Rigoudy; Gaspard Dussert; Abdelbaki Benyoub; Aurélien Besnard; Carole Birck; Jérome Boyer; Yoann Bollet; Yoann Bunz; Gérard Caussimont; Elias Chetouane; Jules Chiffard Carriburu; Pierre Cornette; et al. (European Journal of Wildlife Research, 2023)

Persistent headaches one year after bacterial meningitis: prevalence, determinants and impact on quality of life - Rémi Nguyen Van; Sarah Tubiana; Thomas De Broucker; Joseph Cédric; Carine Roy; Marie-Caroline Meyohas; Thierry Prazuck; Catherine Chirouze; Bruno Hoen; Xavier Duval; Matthieu Revest; Bruno Mourvillier; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

Hedgerows interact with forests to shape the abundance of mesopredators and their predation rate on eggs in farmland landscapes - Carolina Bravo; Mathieu Sarasa; Vincent Bretagnolle; Olivier Pays (Science of The Total Environment, 2023)

The environment: A vector of phenotypic disparity during the settlement phase of coral reef fishes - Mathieu Reynaud; Emma Gairin; David Lecchini; Vincent Laudet; Bruno Frédérich (Journal of Experimental Marine Biology and Ecology, 2023)

Trophic interactions between native newts and introduced mosquitofish suggest invaded ponds may act as demographic sinks - Benjamin Lejeune; Vincent Clément; Thomas Nothomb; Gilles Lepoint; Mathieu Denoël (Biological Invasions, 2023)

The global EPTO database: Worldwide occurrences of aquatic insects - Afroditi Grigoropoulou; Suhaila Ab Hamid; Raúl Acosta; Emmanuel Olusegun Akindele; Salman A. Al‐Shami; Florian Altermatt; Giuseppe Amatulli; David G. Angeler; Francis O. Arimoro; Jukka Aroviita; Anna Astorga‐Roine; Rafael Costa Bastos; et al. (Global Ecology and Biogeography, 2023)
Motivation Aquatic insects comprise 64% of freshwater animal diversity and are widely used as bioindicators to assess water quality impairment and freshwater ecosystem health, as well as to test ecological hypotheses. Despite their importance, a comprehensive, global database of aquatic insect occurrences for mapping freshwater biodiversity in macroecological studies and applied freshwater research is missing. We aim to fill this gap and present the Global EPTO Database , which includes worldwide geo‐referenced aquatic insect occurrence records for four major taxa groups: Ephemeroptera, Plecoptera, Trichoptera and Odonata (EPTO). Main type of variables contained A total of 8,368,467 occurrence records globally, of which 8,319,689 (99%) are publicly available. The records are attributed to the corresponding drainage basin and sub‐catchment based on the Hydrography90m dataset and are accompanied by the elevation value, the freshwater ecoregion and the protection status of their location. Spatial location and grain The database covers the global extent, with 86% of the observation records having coordinates with at least four decimal digits (11.1 m precision at the equator) in the World Geodetic System 1984 (WGS84) coordinate reference system. Time period and grain Sampling years span from 1951 to 2021. Ninety‐nine percent of the records have information on the year of the observation, 95% on the year and month, while 94% have a complete date. In the case of seven sub‐datasets, exact dates can be retrieved upon communication with the data contributors. Major taxa and level of measurement Ephemeroptera, Plecoptera, Trichoptera and Odonata, standardized at the genus taxonomic level. We provide species names for 7,727,980 (93%) records without further taxonomic verification. Software format The entire tab‐separated value (.csv) database can be downloaded and visualized at https://glowabio.org/project/epto_database/ . Fifty individual datasets are also available at https://fred.igb‐berlin.de , while six datasets have restricted access. For the latter, we share metadata and the contact details of the authors.

A research-action process to implement priority areas for alien plant clearing on Reunion Island - Pauline Fenouillas; Claudine Ah-Peng; Elise Amy; Isabelle Bracco; Laurent Calichiama; Emilie Cazal; Mélodie Gosset; Florent Ingrassia; Christophe Lavergne; Benoit Lequette; Jean-Cyrille Notter; Jean-Marie Pausé; et al. (Biological Invasions, 2023)

Correction to: Catch-Up Saccades in Vestibular Hypofunction: A Contribution of the Cerebellum? - Ruben Hermann; Camille Robert; Vincent Lagadec; Mathieu Dupre; Denis Pelisson; Caroline Froment Tilikete (The Cerebellum, 2023)

Catch-Up Saccades in Vestibular Hypofunction: A Contribution of the Cerebellum? - Ruben Hermann; Camille Robert; Vincent Lagadec; Mathieu Dupre; Denis Pelisson; Caroline Froment Tilikete (The Cerebellum, 2023)
Long-term deficits of the vestibulo-ocular reflex (VOR) elicited by head rotation can be partially compensated by catch-up saccades (CuS). These saccades are initially visually guided, but their latency can greatly decrease resulting in short latency CuS (SL-CuS). It is still unclear what triggers these CuS and what are the underlying neural circuits. In this study, we aimed at evaluating the impact of cerebellar pathology on CuS by comparing their characteristics between two groups of patients with bilateral vestibular hypofunction, with or without additional cerebellar dysfunction. We recruited 12 patients with both bilateral vestibular hypofunction and cerebellar dysfunction (BVH-CD group) and 12 patients with isolated bilateral vestibular hypofunction (BVH group). Both groups were matched for age and residual VOR gain. Subjects underwent video head impulse test recording of the horizontal semicircular canals responses as well as recording of visually guided saccades in the step, gap, and overlap paradigms. Latency and gain of the different saccades were calculated. The mean age for BVH-CD and BVH was, respectively, 67.8 and 67.2 years, and the mean residual VOR gain was, respectively, 0.24 and 0.26. The mean latency of the first catch-up saccade was significantly longer for the BVH-CD group than that for the BVH group (204 ms vs 145 ms, p < 0.05). There was no significant difference in the latency of visually guided saccades between the two groups, for none of the three paradigms. The gain of covert saccades tended to be lower in the BVH-CD group than in BVH group ( t test; p = 0.06). The mean gain of the 12° or 20° visually guided saccades were not different in both groups. Our results suggest that the cerebellum plays a role in the generation of compensatory SL-CuS observed in BVH patients.

Pesticide impacts on avian species with special reference to farmland birds: a review - Jérôme Moreau; Juliette Rabdeau; Isabelle Badenhausser; Mathieu Giraudeau; Tuul Sepp; Malaury Crépin; Agathe Gaffard; Vincent Bretagnolle; Karine Monceau (Environmental Monitoring and Assessment, 2022)

Estimating Bycatch From Non-representative Samples (II): A Case Study of Pair Trawlers and Common Dolphins in the Bay of Biscay - Etienne Rouby; Laurent Dubroca; Thomas Cloâtre; Sebastien Demanèche; Mathieu Genu; Kelly Macleod; Hélène Peltier; Vincent Ridoux; Matthieu Authier (Frontiers in Marine Science, 2022)
Marine megafauna plays an important functional role in marine ecosystems as top predators but are threatened by a wide range of anthropogenic activities. Bycatch, the incidental capture of non-targeted species in commercial and recreational fisheries, is of particular concern for small cetacean species, such as dolphins and porpoises. In the North-East Atlantic, common dolphin ( Delphinus delphis , Linné 1758) bycatch has been increasing and associated with large numbers of animals stranding during winter on the French Atlantic seashore since at least 2017. However, uncertainties around the true magnitude of common dolphin bycatch and the fisheries involved have led to delays in the implementation of mitigation measures. Current data collection on dolphin bycatch in France is with non-dedicated observers deployed on vessels for the purpose of national fisheries sampling programmes. These data cannot be assumed representative of the whole fisheries' bycatch events. This feature makes it difficult to use classic ratio estimators since they require a truly randomised sample of the fishery by dedicated observers. We applied a newly developed approach, regularised multilevel regression with post-stratification, to estimate total bycatch from unrepresentative samples and total fishing effort. The latter is needed for post-stratification and the former is analysed in a Bayesian framework with multilevel regression to regularise and better predict bycatch risk. We estimated the number of bycaught dolphins for each week and 10 International Council for the Exploration of the Sea (ICES) divisions from 2004 to 2020 by estimating jointly bycatch risk, haul duration, and the number of hauls per days at sea (DaS). Bycatch risk in pair trawlers flying the French flag was the highest in winter 2017 and 2019 and was associated with the longest haul durations. ICES divisions 8.a and 8.b (shelf part of the Bay of Biscay) were estimated to have the highest common dolphin bycatch. Our results were consistent with independent estimates of common dolphin bycatch from strandings. Our method show cases how non-representative observer data can nevertheless be analysed to estimate fishing duration, bycatch risk and, ultimately, the number of bycaught dolphins. These weekly-estimates improve upon current knowledge of the nature of common dolphin bycatch and can be used to inform management and policy decisions at a finer spatio-temporal scale than has been possible to date. Our results suggest that limiting haul duration, especially in winter, could serve as an effective mitigation strategy.

Linking personality and health to use of space in the gray partridge: perspectives for management - Clément Harmange; Vincent Bretagnolle; Olivier Pays; Mathieu Sarasa; Jérôme Moreau (European Journal of Wildlife Research, 2021)

Environmental DNA metabarcoding for freshwater bivalves biodiversity assessment: methods and results for the Western Palearctic (European sub-region) - Vincent Prié; Alice Valentini; Manuel Lopes-Lima; Elsa Froufe; Mathieu Rocle; Nicolas Poulet; Pierre Taberlet; Tony Dejean (Hydrobiologia, 2021)

Altered expression of fractalkine in HIV-1-infected astrocytes and consequences for the virus-related neurotoxicity - Vincent Sénécal; Corinne Barat; Marie-Thérèse Gagnon; François Vanasse; Mathieu Leboeuf; David Gosselin; Michel J. Tremblay (Journal of NeuroVirology, 2021)

Latitudinal variation in plant defence against herbivory in a marine foundation species does not follow a linear pattern: The importance of resource availability - Gema Hernán; María J. Ortega; Jeremy Henderson; Josep Alós; Katharyn Boyer; Stephanie Cimon; Vincent Combes; Mathieu Cusson; Clara M. Hereu; Margot Hessing‐Lewis; Kevin Hovel; Pablo Jorgensen; et al. (Global Ecology and Biogeography, 2021)
Aim Studies on latitudinal patterns in plant defence have traditionally overlooked the potential effect that resource availability may have in shaping plant defence. Likewise, latitudinal patterns of tolerance traits have rarely been studied, yet they can be a critical component of plant defence. Therefore, the aim of our study was to examine latitudinal variation in the production of tolerance and resistance traits against herbivory along a latitudinal range and a natural gradient of resource availability from upwelling conditions. Location North America (Canada, USA, Mexico). Time period Summer months of 2015. Major taxa used The seagrass Zostera marina . Methods We conducted experiments simulating macroherbivore (e.g., bird, fish) damage on the seagrass Z. marina at 10 sites across the Eastern Pacific coast (Canada–Mexico) and Quebec and analysed several traits related to resistance and tolerance strategies against herbivory. In addition, we examined the effects of potential seagrass changes in defence strategies by performing a series of feeding experiments with mesoherbivores in a subset of sites. Results We found that eelgrass resistance defences did not follow a linear latitudinal pattern but rather followed a bell‐shaped curve which correlated with bottom‐up control. In sites with higher nutrient availability, plants allocated resources to tolerance strategies and had lower resistance traits. Furthermore, seagrasses did not respond linearly to increased herbivory pressure; while they tolerated moderate levels of herbivory, they underwent a significant reduction in tolerance and resistance under high herbivory levels, which also made them more susceptible to consumers in feeding experiments. Main conclusions Our results highlight the importance that nutrient availability has in shaping latitudinal patterns of plant defence against herbivory and show how these defences may not respond linearly to increased herbivory pressure in seagrasses.

Argo Data 1999–2019: Two Million Temperature-Salinity Profiles and Subsurface Velocity Observations From a Global Array of Profiling Floats - Annie P. S. Wong; Susan E. Wijffels; Stephen C. Riser; Sylvie Pouliquen; Shigeki Hosoda; Dean Roemmich; John Gilson; Gregory C. Johnson; Kim Martini; David J. Murphy; Megan Scanderbeg; T. V. S. Udaya Bhaskar; et al. (Frontiers in Marine Science, 2020)

Muskox status, recent variation, and uncertain future - Christine Cuyler; Janice Rowell; Jan Adamczewski; Morgan Anderson; John Blake; Tord Bretten; Vincent Brodeur; Mitch Campbell; Sylvia L. Checkley; H. Dean Cluff; Steeve D. Côté; Tracy Davison; et al. (Ambio, 2020)

De-escalation and discontinuation strategies in high-risk neutropenic patients: an interrupted time series analyses of antimicrobial consumption and impact on outcome - Giulia la Martire; Christine Robin; Nadia Oubaya; Raphaël Lepeule; Florence Beckerich; Mathieu Leclerc; Walid Barhoumi; Andréa Toma; Cécile Pautas; Sébastien Maury; Wiem Akrout; Catherine Cordonnier-Jourdin; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

A Decision Support Tool Facilitating Medicine Design for Optimal Acceptability in The Older Population - Thibault Vallet; Emilie Belissa; Sandra Laribe-Caget; Alain Chevallier; François-Xavier Chedhomme; Patrick Leglise; Matthieu Piccoli; Hugues Michelon; Vanessa Bloch; Sylvie Meaume; Anne-Sophie Grancher; Nathalie Bachalat; et al. (Pharmaceutical Research, 2018)

Outcome after epilepsy surgery at the University Hospitals Leuven 1998–2012 - Lynn Vermeulen; Johannes van Loon; Tom Theys; Jan Goffin; Kathleen Porke; Koen Van Laere; Karolien Goffin; Mathieu Vandenbulcke; Vincent Thijs; Wim Van Paesschen (Acta Neurologica Belgica, 2016)

Investigating the Neural Correlates of the Stroop Effect with Magnetoencephalography - Sophie Galer; Marc Op De Beeck; Charline Urbain; Mathieu Bourguignon; Noémie Ligot; Vincent Wens; Brice Marty; Patrick Van Bogaert; Philippe Peigneux; Xavier De Tiège (Brain Topography, 2015)

International cross-validation of a BOD5 surrogate - Mathieu Muller; Sihem Bouguelia; Romy-Alice Goy; Alison Yoris; Jeanne Berlin; Perrine Meche; Vincent Rocher; Sharon Mertens; Yves Dudal (Environmental Science and Pollution Research, 2014)

Inter- and Intra-Subject Variability of Neuromagnetic Resting State Networks - Vincent Wens; Mathieu Bourguignon; Serge Goldman; Brice Marty; Marc Op de Beeck; Catherine Clumeck; Alison Mary; Philippe Peigneux; Patrick Van Bogaert; Matthew J. Brookes; Xavier De Tiège (Brain Topography, 2014)

Comprehensive Functional Mapping Scheme for Non-Invasive Primary Sensorimotor Cortex Mapping - Mathieu Bourguignon; Veikko Jousmäki; Brice Marty; Vincent Wens; Marc Op de Beeck; Patrick Van Bogaert; Mustapha Nouali; Thierry Metens; Boris Lubicz; Florence Lefranc; Michael Bruneau; Olivier De Witte; et al. (Brain Topography, 2013)

Alkylphenolic compounds and bisphenol A contamination within a heavily urbanized area: case study of Paris - Mathieu Cladière; Johnny Gasperi; Catherine Lorgeoux; Céline Bonhomme; Vincent Rocher; Bruno Tassin (Environmental Science and Pollution Research, 2013)

Erratum to: A comprehensive overview of the spatial and temporal variability of apple bud dormancy release and blooming phenology in Western Europe - Jean Michel Legave; Michael Blanke; Danilo Christen; Daniela Giovannini; Vincent Mathieu; Robert Oger (International Journal of Biometeorology, 2013)

A comprehensive overview of the spatial and temporal variability of apple bud dormancy release and blooming phenology in Western Europe - Jean Michel Legave; Michael Blanke; Danilo Christen; Daniela Giovannini; Vincent Mathieu; Robert Oger (International Journal of Biometeorology, 2013)

In Vitro Screening for Drug-Induced Depression and/or Suicidal Adverse Effects: A New Toxicogenomic Assay Based on CE-SSCP Analysis of HTR2C mRNA Editing in SH-SY5Y Cells - Laurent Cavarec; Laurent Vincent; Claudia Le Borgne; Camille Plusquellec; Nathalie Ollivier; Priscilla Normandie-Levi; Frédéric Allemand; Nicolas Salvetat; Eve Mathieu-Dupas; Franck Molina; Dinah Weissmann; Jean-François Pujol (Neurotoxicity Research, 2013)

Mineralogical study and leaching behavior of a stabilized harbor sediment with hydraulic binder - Vincent Chatain; Mostafa Benzaazoua; Marie Loustau Cazalet; Hassan Bouzahzah; Cécile Delolme; Mathieu Gautier; Denise Blanc; Christine de Brauer (Environmental Science and Pollution Research, 2013)

Alpha7-nicotinic receptors modulate nicotine-induced reinforcement and extracellular dopamine outflow in the mesolimbic system in mice - Morgane Besson; Vincent David; Mathieu Baudonnat; Pierre Cazala; Jean-Philippe Guilloux; Christelle Reperant; Isabelle Cloez-Tayarani; Jean-Pierre Changeux; Alain M. Gardier; Sylvie Granon (Psychopharmacology, 2012)

Gaudeamus lavocati sp. nov. (Rodentia, Hystricognathi) from the early Oligocene of Zallah, Libya: first African caviomorph? - Pauline Coster; Mouloud Benammi; Vincent Lazzari; Guillaume Billet; Thomas Martin; Mustafa Salem; Awad Abolhassan Bilal; Yaowalak Chaimanee; Mathieu Schuster; Xavier Valentin; Michel Brunet; Jean-Jacques Jaeger (The Science of Nature, 2010)

Effects of access to preen gland secretions on mallard plumage - Mathieu Giraudeau; Camille Duval; Noel Guillon; Vincent Bretagnolle; Claude Gutierrez; Philipp Heeb (The Science of Nature, 2010)

Analyses of associations with asthma in four asthma population samples from Canada and Australia - Denise Daley; Mathieu Lemire; Loubna Akhabir; Moira Chan-Yeung; Jian Qing He; Treena McDonald; Andrew Sandford; Dorota Stefanowicz; Ben Tripp; David Zamar; Yohan Bosse; Vincent Ferretti; et al. (Human Genetics, 2009)

Rhod-5N as a Fluorescent Molecular Sensor of Cadmium(II) Ion - Mathieu Soibinet; Vincent Souchon; Isabelle Leray; Bernard Valeur (Journal of Fluorescence, 2008)

Hydrocarbons and Metals in Atmospheric Deposition and Roof Runoff in Central Paris - Vincent Rocher; Sam Azimi; Johnny Gasperi; Loïc Beuvin; Mathieu Muller; Régis Moilleron; Ghassan Chebbo (Water, Air, & Soil Pollution, 2004)

Mangroves of Oman during the late Holocene; climatic implications and impact on human settlements - Anne-Marie Lézine; Jean-François Saliège; Robert Mathieu; Thibaut-Louis Tagliatela; Sophie Mery; Vincent Charpentier; Serge Cleuziou (Vegetation History and Archaeobotany, 2002)